PRIORITIZING DEVELOPMENT NEEDS IN IRAQ, ESPECIALLY IN RURAL AREAS - Sattar Awad Dhmaid; Nadia Kadhim Awad (Scholars Digest Publishing, 2024)
This study aims to conduct an assessment of the general situation in Iraq regarding education, health, and other public services in rural areas. For development in Iraq, especially in rural areas, the focus was placed on: (decentralizing health and educational services to alleviate development problems, improving water and sanitation infrastructure, and preparing educational programs directed towards practical knowledge and skills required and identified in the current labour market, continuing efforts to improve access to intervention health, insurance, health care, development of technology transfer programs and other support efforts to improve indigenous rural communities. We believe, however, that by implementing our four proposed policies above, the Iraqi government can continue the momentum toward greater inclusivity and socioeconomic equity for the poorest poor in the future.
Keywords: decentralization, universal health coverage, water and sanitation.